Analisis Strategi Mengajar pada Mata Kuliah Pengantar Akuntansi I Materi Siklus Akuntansi di Program Studi Pendidikan - Manuhutu, Venlly Debora; Tomasoa, Theodora Florence; Manuhuttu, Silvia (Universitas Pattimura, 2024)
This study aims to analyze the teaching strategies employed by lecturers in the Introduction to Accounting I course, particularly on the topic of the Accounting Cycle, within the Economics Education Study Program at FKIP Pattimura University. The course is complex and requires students to systematically understand the stages of the accounting process. A qualitative descriptive method was used, involving observation, interviews, and documentation. The findings reveal that the teaching strategies include interactive lectures, group discussions, problem-solving exercises, and the use of visual media such as slides and videos. These strategies are considered effective in helping students grasp basic accounting concepts and map out the accounting cycle from transaction recording to financial statement preparation. Active student participation in discussions and hands-on practice plays a crucial role in improving learning outcomes. However, challenges remain in diversifying instructional approaches and integrating educational technology. The study recommends enhancing lecturers' pedagogical competencies and developing digital-based teaching methods to improve the quality of accounting education in higher education institutions.